Land-constrained growth in a developing economy: A Kaldorian perspective - Isha Gupta (PSL Quarterly Review, 2022)
The paper develops a two-sector model of economic growth, using agriculture and industry. The distinguishing feature in this analysis is that land is an essential input in the agricultural sector, but it is also used in the production process of industrial sector, which is assumed to be imperfectly competitive. The significant role of land allocations is highlighted for a developing economy like India, where any constraint on land transfers from agricultural to non-agricultural sectors imposes a constraint on the overall growth process of the economy. Using the two-sector Kaldorian framework, we analyse the complementary interactions between agriculture and industry through trade flows, labour movements, and land transfers in this setup. We characterize the balanced growth path for such an economy in the long run using two scenarios: a) equilibrium growth with fixed distribution of land by the centralized authority in each sector and b) equilibrium growth with inter-sectoral land transfers accompanied by land-saving innovations in each sector.
Keywords: E10; O40; O41; Q150; 330; Two-sector Growth Model; Agriculture; Industry; Land-constraint; Balanced Growth Path